Faktor Risiko Hipertensi pada Usia 50 Sampai 70 Tahun di Wilayah Puskesmas Bahkapul Kota Pematangsiantar - Nasution, Dian Permata; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Ginting, Isaharpika Br; Hendri, Hendri (Jurnal Riset Hesti Medan, 2024)
Hypertension is a global problem, and its prevalence continues to rise to alarming levels. This condition is often referred to as the “silent killer” because patients do not experience symptoms or complaints, so they are unaware that they have hypertension, and many people only find out after complications have already developed. Hypertension is the leading cause of death worldwide each year, particularly among the elderly. This is why the WHO has set one of its global targets for non-communicable diseases as reducing the prevalence of hypertension by 33% between 2010 and 2030 (WHO, 2023). Objective: This study aims to identify the factors influencing the risk of hypertension in the elderly. Methods: A systematic literature review was conducted. Studies were identified through searches on Google Scholar and PubMed for publications from 2019 to 2023 using the keywords “Factors,” “Hypertension,” and “Elderly.” A total of 16,100 results were found on Google Scholar and 959 on PubMed, with 10 journals meeting the eligibility criteria. Results: Based on the journal review, the incidence of hypertension can be influenced by several factors, such as age, genetics, gender, excessive salt and fat intake, obesity, stress, physical activity, smoking, and alcohol and coffee consumption. Conclusion: An individual is more likely to develop hypertension if there is a family history of the condition. Additionally, individuals over the age of 65 with conditions such as obesity and kidney disease are at higher risk of developing hypertension. Once diagnosed with hypertension, an individual must adopt a healthy lifestyle as part of the management of blood pressure control. We can control hypertension risk factors through a healthy diet and lifestyle, avoiding